112PA retrospective analysis of the association between perioperative, post adjuvant carcinoembryonic antigen level and prognosis in stage III colorectal cancer. (24th November 2019) - Kozuki, R; Shinozaki, E; Osumi, H; Wakatuki, T; Suenaga, M; Ogura, M; Suzuki, T; Nakayama, I; Takahari, D; Chin, K; Nagasaki, T; Konishi, T; et al.
Abstract: Background: Carcinoembryonic antigen (CEA) is the most widespread tumour marker of colorectal cancer, however, it is not helpful to judge for recurrence of the disease because of low sensitivity and specificity. It is recommended for patients who were diagnosed with pStage III colorectal cancer to receive adjuvant chemotherapy after curative resection and to measure CEA every 3 months. Moreover, It is reported that postoperative CEA level is more informative than preoperative CEA level about the impact for prognosis but the association between postoperative, post adjuvant CEA level and the prognosis is still unclear. This study aimed to evaluate whether perioperative and post adjuvant CEA level was useful for estimation of the prognosis in stage III CRC. Methods: This retrospective study was conducted at the Cancer Institute Hospital of JFCR. A total of 567 consecutive patients who underwent curative resection for stage III colon adenocarcinoma and adjuvant chemotherapy in our hospital from March 2005 to December 2013 were identified. The patients who received bevacizumab as adjuvant chemotherapy and didn't measure CEA were excluded. Results: The 3-year DFS rate in patients with normal preoperative CEA is superior to patients with high preoperative CEA (HR:1.59;95%CI:1.10-2.31, p = 0.014). There was no significant difference in the 5-year OD between the two groups (HR1.17;95%CI:0.62–2.20, p = 0.63). The 3-year DFS rate and 5-year OS rate in patients with normal postoperative CEA were superior to patients with high postoperative CEA (HR:2.18;95%CI:1.23–3.88, p = 0.0079, and HR:2.40;95%CI:1.02–5.69, p = 0.046). The 3-year DFS in patients with normal postadjuvant CEA was superior to patients with high postadjuvant CEA(HR1.79;95%CI:1.23–3.88, p = 0.022), whereas regarding the 5-year OS there was no significant difference between the two groups (HR2.10;95%CI:0.98–4.53, p = 0.057).In the multivariate analysis, the histological type and N-stage were predictive factors of OS. Conclusions: High postoperative and post adjuvant CEA level may be negative prognosis factors for OS in patients who underwent curative resection for stage III CRC. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.